Ewing’s Sarcoma with Extension into Superior Vena Cava and Right Atrium - Atsumi, Yukari (Indian J Surg Oncol, 2019)
Ewing sarcoma is rarely shown to develop this intravascular extension so the decision of the initial treatment is more difficult. We report a 7-year-old boy of this sarcoma with extension into superior vena cava (SVC) and right atrium (RA), who was successfully treated with initial surgery. Intravascular extension was observed from the azygous vein to SVC and finally RA. The removal of the intravascular extension was done, 7 days before chemotherapy was started. The initial surgery for the intravascular extension may have decreased a risk of pulmonary tumor embolism and this made the chemotherapy done safe in this patient.